СОВРЕМЕННЫЕ НАУЧНЫЕ ВОЗМОЖНОСТИ ИЗУЧЕНИЯ ЧЕЛОВЕКА И ЧЕЛОВЕЧЕСКОГО КАПИТАЛА - Ковылов (Kovylov Vladimir), Владимир Константинович (Географический вестник=Geographical bulletin, 2017)
В статье делается акцент на повышении внимания к проблеме изучения человека и человеческого капитала как главного элемента национального богатства страны. Определяется круг современных наук и научных направлений, которые изучают данные вопросы. Большое значение уделяется возможностям внедрения гипотез и теорий в общественно-географические исследования и их важности для современной географии. THE MODERN SCIENTIFIC OPPORTUNITIES IN STUDYING OF MAN AND HUMAN CAPITAL In modernRussiathere are trends of increasing of attention to the problems of human capital’s studying, the major component of national wealth. Population geography, social geography are traditional disciplines. At the same time geography of quality and image of life, behaviorist geography are forming now. By the way, a lot of new science and scientific directions have appeared beyond human geography. Their subjects are deal with the problems of universal studying of human properties and man’s qualitative characteristics. In the abstract the author has paid much attention to human genetics, medical genetics and genogeography, which allow to determine the determining stability of human genofond behind global problems. Anthropology, economic anthropology and ethnogeography consider Man as a biosocial essence. As separated direction the author has considered sociology of American scholar Pitirim Sorokin. The author has found wide links between sciences, studying globalized and ecologic processes, and social-economic geography. He also has noted human eniology, cosmoenergetics and evolutionary electrodymanics. In conclusion, the author has pointed out “conducted” role of geographical science in system of knowledge about Man. Whereby the examples of achievements of evolutionary electrodynamics he has showed transformation in studying from ergatic capital to human.